Negative photosensitive resin composition
By using alkaline -containing polymers, cross -linked compounds, and lithographic polymerizers at 100 ° C to bake temperature at 100 ° C, it solves the problem that the existing technologies are difficult to satisfy multiple characteristics under low temperature heating at low temperature heating at low temperature heating. The formation of high transparency, solvent resistance, and high sensitivity membrane formation.
Patent Information
- Application Number
- CN201980056292.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-08-30
- Filing Date
- 2019-07-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2039-07-30
AI Technical Summary
The prior art is difficult to meet the requirements of high transparency, solvent resistance, sensitivity characteristics and unexposed residues in electronic devices such as CCD/CMOS image sensors under low temperature heating below 100°C.
Using negative photosensitive resin compositions containing alkaline -soluble polymers, at least 2 cross -linking compounds, and at least one type of photocardiac cause of light polymerization. By optimizing the amount of these ingredients, it is formed to have high transparency at a baking temperature at 100 ° C. Sex, sensitivity and low residue film.
The membrane obtained by the baking temperature at 100 ° C is highly transparent, solveily resistant, sensitivity characteristics, and less residual residues of the exposure, which is suitable for forming high -performance microscopy.
Smart Images

Figure BDA0002953450740000031 
Figure BDA0002953450740000032 
Figure BDA0002953450740000171
Abstract
Description
Technical Field
[0001] The present invention relates to a negative photosensitive resin composition comprising an alkali-soluble polymer, at least two crosslinking compounds, at least one photopolymerization initiator, and a solvent, and particularly to a negative photosensitive resin composition for forming a microlens. Background Art
[0002] For a long time, in electronic devices such as CCD / CMOS image sensors, microlenses are provided to improve the light-gathering efficiency. As one of the methods for manufacturing microlenses for CCD / CMOS image sensors, the etch-back method is known (Patent Document 1 and Patent Document 2). That is, a resist pattern is formed on a microlens resin layer formed on a color filter, and the resist pattern is reflowed by heat treatment to form a lens pattern. The lens pattern formed by reflowing the resist pattern is used as an etching mask, and the lower microlens resin layer is etched back, and the lens pattern shape is transferred to the microlens resin layer, thereby manufacturing a microlens. Such a microlens requires various properties such as chemical resistance and high transparency.
[0003] In addition, when a film is patterned at an arbitrary position on an electronic device such as a CCD / CMOS image sensor, a liquid crystal display, and an organic EL display, photolithography is required. For such a photosensitive material, it is required to be able to form a pattern at a low exposure (sensitivity characteristics) and to suppress the generation of residues after alkali development.
[0004] In addition, a photosensitive resin composition for forming a microlens containing a maleimide copolymer (Patent Document 3) and a positive resist composition containing a triazine skeleton (Patent Document 4) have been proposed. However, in order to satisfy the above-mentioned various characteristics, especially solvent resistance, these patent documents require high-temperature heating exceeding 100°C, for example, 140°C to 260°C, and the above-mentioned characteristics cannot be satisfied by low-temperature heating below 100°C.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 1-10666
[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 6-112459
[0009] Patent Document 3: Japanese Patent No. 5867735
[0010] Patent Document 4: Japanese Patent No. 5673963 Summary of the invention
[0011] Problems to be solved by the invention
[0012] The present invention has been made based on the above situation, and the problem to be solved is to provide a negative photosensitive resin composition that can produce a film having significantly improved high transparency, solvent resistance, sensitivity characteristics, and residue in unexposed areas at a baking temperature of 100°C.
[0013] Methods for solving problems
[0014] The inventors of the present invention have conducted intensive research to solve the above-mentioned problems and have completed the present invention. That is, the present invention is a negative photosensitive resin composition, which contains the following (A) component, 80% to 90% by mass of the following (B) component relative to 100% by mass of the (A) component, 3% to 20% by mass of the following (C) component relative to 100% by mass of the total amount of the (B) component, and a solvent.
[0015] (A) Component: Alkali-soluble polymer
[0016] Component (B): at least two crosslinking compounds having two or more polymerizable groups selected from the group consisting of acryloyloxy, methacryloyloxy, allyl and vinyl groups in one molecule
[0017] Component (C): at least one photopolymerization initiator
[0018] The at least two crosslinkable compounds include, for example, a crosslinkable compound having two acryloyloxy groups or methacryloyloxy groups as the polymerizable groups in one molecule, and a crosslinkable compound having three or more acryloyloxy groups or methacryloyloxy groups as the polymerizable groups in one molecule.
[0019] The alkali-soluble polymer has a structural unit selected from the following formula (1a), formula (1b), formula (1c), formula (1d) and formula (1e), for example.
[0020]
[0021] (Where R 1 represents a hydrogen atom or a methyl group, A represents an -O- group or an -NH- group, X represents a single bond, an alkylene group having 1 to 3 carbon atoms, or a divalent linking group containing an alkyleneoxy group having 1 to 3 carbon atoms, and Z 1 represents hydroxyphenyl or carboxyphenyl, Z 2 represents hydroxyphenyl, carboxyphenyl or carboxyl, Z 3 represents a hydrogen atom, a hydroxyphenyl group or a carboxyphenyl group. )
[0022] The divalent linking group is, for example, the above-mentioned alkyleneoxy group having 1 to 3 carbon atoms, or a group in which two or more of the alkyleneoxy groups having 1 to 3 carbon atoms are bonded.
[0023] The alkali-soluble polymer is, for example, a copolymer further having a structural unit selected from the following formula (2a), formula (2b) and formula (2c), which is different from the above-mentioned structural unit.
[0024]
[0025] (Where R 1 represents a hydrogen atom or a methyl group, A represents an -O- group or an -NH- group, X represents a single bond, an alkylene group having 1 to 3 carbon atoms, or a divalent linking group containing an alkyleneoxy group having 1 to 3 carbon atoms, and Z 4 represents a linear organic group having 1 to 3 carbon atoms, or a branched or cyclic organic group having 3 to 14 carbon atoms.
[0026] The divalent linking group is, for example, an alkyleneoxy group having 1 to 3 carbon atoms, or a group formed by bonding two or more alkyleneoxy groups having 1 to 3 carbon atoms. The organic group may have at least one heteroatom such as a nitrogen atom or an oxygen atom, and may have a double bond or a triple bond between two carbon atoms or between a carbon atom and a heteroatom. Examples of the cyclic organic group include aromatic hydrocarbon groups, alicyclic hydrocarbon groups, bridged hydrocarbon groups, and heterocyclic groups.
[0027] The negative photosensitive resin composition of the present invention is used to form a microlens, for example.
[0028] In addition, the present invention is a method for producing a microlens, which comprises the following steps: a step of coating the above-mentioned negative photosensitive resin composition on a substrate and pre-baking to form a resin film; a step of exposing the above-mentioned resin film through a mask; a step of developing the above-mentioned exposed resin film using an alkaline developer; and a step of exposing the entire surface of the above-mentioned developed resin film.
[0029] After or before the step of exposing the entire surface of the developed resin film, a step of post-baking the resin film may be further included.
[0030] Effects of the Invention
[0031] The negative photosensitive resin composition of the present invention optimizes the addition amounts of the alkali-soluble polymer, at least two crosslinking compounds, and at least one photopolymerization initiator, so that a film obtained by using the composition at a baking temperature of 100° C. can be highly transparent, highly sensitive, with little residue in the unexposed portion, and excellent solvent resistance. Therefore, the negative photosensitive resin composition of the present invention is suitable as a material for forming a microlens. DETAILED DESCRIPTION
[0032] The present invention is a negative photosensitive resin composition containing component (A), component (B) of 80% to 90% by mass relative to 100% by mass of the component (A), component (C) of 3% to 20% by mass relative to 100% by mass of the total amount of component (B), and a solvent. The following describes the details of each component of the present invention. The solid content after removing the solvent from the negative photosensitive resin composition of the present invention is usually 1% to 50% by mass. In this specification, the components of the negative photosensitive resin composition of the present invention other than the solvent are defined as solid content.
[0033] <(A)Component>
[0034] The component (A) in the negative photosensitive resin composition of the present invention is an alkali-soluble polymer. The polymer is a polymer of raw material monomers containing a monomer having an alkali-soluble group and any other monomers. The alkali-soluble polymer of the component (A) only needs to have an alkali-soluble group, and there is no particular limitation on the skeleton of the main chain of the polymer and the type of the side chain constituting the polymer. The weight average molecular weight of the above-mentioned alkali-soluble polymer is, for example, 1000 to 50000, preferably 3000 to 40000. In addition, the weight average molecular weight is a value obtained by gel permeation chromatography (GPC) using polystyrene as a standard sample.
[0035] Examples of the monomer having an alkali-soluble group include a monomer having a carboxyl group, a monomer having a phenolic hydroxyl group, a monomer having an acid anhydride group, and a monomer having a maleimide group.
[0036] Examples of the monomer having a carboxyl group include acrylic acid, methacrylic acid, crotonic acid, mono-(2-(acryloyloxy)ethyl)phthalate, mono-(2-(methacryloyloxy)ethyl)phthalate, N-(carboxyphenyl)maleimide, N-(carboxyphenyl)methacrylamide, N-(carboxyphenyl)acrylamide, and 4-vinylbenzoic acid.
[0037] Examples of the monomer having a phenolic hydroxyl group include hydroxystyrene, N-(hydroxyphenyl)acrylamide, N-(hydroxyphenyl)methacrylamide, and N-(hydroxyphenyl)maleimide.
[0038] Examples of the monomer having an acid anhydride group include maleic anhydride and itaconic anhydride.
[0039] Examples of the monomer having a maleimide group include the above-mentioned N-(carboxyphenyl)maleimide and N-(hydroxyphenyl)maleimide, and maleimide.
[0040] Among the above-mentioned monomers having an alkali-soluble group, a polymer containing at least one monomer selected from the group consisting of acrylic acid, methacrylic acid, maleic anhydride, and maleimide is preferred.
[0041] In addition, the alkali-soluble polymer of component (A) may be a copolymer of the above-mentioned monomer having an alkali-soluble group and other monomers. The copolymer is not limited to a copolymer obtained from two monomers, and may be a terpolymer obtained from three monomers. Specific examples of the above-mentioned other monomers include, for example, acrylate compounds, methacrylate compounds, N-substituted maleimide compounds, acrylonitrile compounds, acrylamide compounds, methacrylamide compounds, styrene compounds, and vinyl compounds. Specific examples of the above-mentioned other monomers are given below, but are not limited thereto.
[0042] Examples of the acrylate compound include methyl acrylate, ethyl acrylate, isopropyl acrylate, benzyl acrylate, naphthyl acrylate, anthracene acrylate, anthracene methyl acrylate, phenyl acrylate, phenoxyethyl acrylate, 2,2,2-trifluoroethyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, isobornyl acrylate, 2-methoxyethyl acrylate, methoxytriglycol acrylate, 2-ethoxyethyl acrylate, tetrahydrofurfuryl acrylate, 3-methoxybutyl acrylate, 2-methyl-2-adamantyl acrylate, Ester, 2-propyl-2-adamantyl acrylate, 8-methyl-8-tricyclodecanyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 4-hydroxybutyl acrylate, 2,3-dihydroxypropyl acrylate, diethylene glycol monoacrylate, 2-(acryloyloxy)ethyl caprolactone, poly(ethylene glycol) ethyl ether acrylate, 5-acryloyloxy-6-hydroxynorbornene-2-carboxy-6-lactone, acryloyloxyethyl isocyanate, 8-ethyl-8-tricyclodecanyl acrylate, glycidyl acrylate.
[0043] Examples of the methacrylate compound include methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, benzyl methacrylate, naphthyl methacrylate, anthracene methacrylate, anthracene methyl methacrylate, phenyl methacrylate, phenoxyethyl methacrylate, 2,2,2-trifluoroethyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, 2-methoxyethyl methacrylate, methoxytriethylene glycol methacrylate, 2-ethoxyethyl methacrylate, tetrahydrofurfuryl methacrylate, 3-methoxybutyl methacrylate, 2-methyl-2-adamantane methacrylate, and the like. ester, γ-butyrolactone methacrylate, 2-propyl-2-adamantyl methacrylate, 8-methyl-8-tricyclodecanyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 2,3-dihydroxypropyl methacrylate, diethylene glycol monomethacrylate, 2-(methacryloyloxy)ethyl caprolactone, poly(ethylene glycol) ethyl ether methacrylate, 5-methacryloyloxy-6-hydroxynorbornene-2-carboxy-6-lactone, methacryloyloxyethyl isocyanate, 8-ethyl-8-tricyclodecanyl methacrylate, glycidyl methacrylate.
[0044] Examples of the vinyl compound include methyl vinyl ether, benzyl vinyl ether, vinyl naphthalene, vinyl anthracene, vinyl biphenyl, vinyl carbazole, 2-hydroxyethyl vinyl ether, phenyl vinyl ether, and propyl vinyl ether.
[0045] Examples of the styrene compound include styrene, methylstyrene, chlorostyrene, and bromostyrene.
[0046] Examples of the N-substituted maleimide compound include N-methylmaleimide, N-phenylmaleimide, and N-cyclohexylmaleimide.
[0047] Examples of the acrylonitrile compound include acrylonitrile.
[0048] In addition, as the addition ratio of the monomer having an alkali-soluble group to other monomers, it is preferred that the monomer having an alkali-soluble group / other monomers = 5 to 50 mass % / 50 to 95 mass %. When the addition ratio of the monomer having an alkali-soluble group to other monomers is too small, the unexposed part does not dissolve in the developer and is likely to become a cause of residual film and residue. In addition, when the addition ratio of the monomer having an alkali-soluble group to other monomers is too large, there is a possibility that the curability of the exposed part is insufficient and a pattern cannot be formed.
[0049] The method for obtaining the alkali-soluble polymer of the component (A) is not particularly limited, but is generally obtained by subjecting raw material monomers including the above-mentioned monomer having an alkali-soluble group to a polymerization reaction in a polymerization solvent, usually at a temperature of 50°C to 110°C.
[0050] The alkali-soluble polymer obtained by the above method has a structural unit selected from the above formula (1a), formula (1b), formula (1c), formula (1d) and formula (1e). The alkali-soluble polymer may further have a structural unit different from the above structural unit and selected from the above formula (2a), formula (2b) and formula (2c).
[0051] The content of the component (A) in the negative photosensitive resin composition of the present invention is usually 48% by mass to 55% by mass based on the solid content of the composition.
[0052] <(B) Ingredient>
[0053] The component (B) in the negative photosensitive resin composition of the present invention is at least two crosslinking compounds having two or more polymerizable groups selected from acryloxy, methacryloyloxy, allyl and vinyl groups in one molecule. As the component (B), a combination of a crosslinking compound having two such polymerizable groups in one molecule and a crosslinking compound having three or more such polymerizable groups in one molecule is preferred. The polymerizable group is present at the molecular terminal of the crosslinking compound.
[0054] The crosslinkable compound of the component (B) is preferably a compound having a weight average molecular weight of 200 to 1,000 from the viewpoint of good compatibility with other components of the negative photosensitive resin composition of the present invention and not affecting developability.
[0055] Examples of the crosslinking compound include dipentaerythritol hexaacrylate, dipentaerythritol hexamethacrylate, dipentaerythritol pentaacrylate, dipentaerythritol pentamethacrylate, pentaerythritol tetraacrylate, pentaerythritol tetramethacrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, pentaerythritol diacrylate, pentaerythritol dimethacrylate, tetramethylolpropane tetraacrylate, tetramethylolpropane tetramethacrylate, and tetramethylolpropane tetraacrylate. Methane tetraacrylate, tetramethylolmethane tetramethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, 1,3,5-triacryloyl hexahydro-s-triazine, 1,3,5-trimethacryloyl hexahydro-s-triazine, tris(hydroxyethylacryloyl)isocyanurate, tris(hydroxyethylmethacryloyl)isocyanurate, triacryloyl formal, trimethacryloyl formal, 1,6-hexanediol acrylate, 1,6-hexanediol methyl Acrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, 2-hydroxypropylene glycol diacrylate, 2-hydroxypropylene glycol dimethacrylate, diethylene glycol diacrylate, diethylene glycol dimethacrylate, isopropylene glycol diacrylate, isopropylene glycol dimethacrylate, triethylene glycol diacrylate, triethylene glycol dimethacrylate, N,N'-bis(acryloyl)cysteine, N,N'-bis( Methacryloyl) cysteine, thiodiglycol diacrylate, thiodiglycol dimethacrylate, bisphenol A diacrylate, bisphenol A dimethacrylate, bisphenol F diacrylate, bisphenol F dimethacrylate, bisphenol S diacrylate, bisphenol S dimethacrylate, bisphenoxyethanol fluorene diacrylate, bisphenoxyethanol fluorene dimethacrylate, diallyl ether bisphenol A, o,o'-diallyl bisphenol A, diallyl maleate, triallyl trimellitate.
[0056] The above-mentioned reciprocal compounds can be produced easily and can be easily obtained as examples, KAYARAD T-1420, KAYARAD DPHA, KAYARAD DPHA-2C, KAYARAD D-310, KAYARAD D-330, KAYARADDPCA-20, KAYARAD DPCA-30, KAYARAD DPCA-60, KAYARAD DPCA-120, KAYARAD DN-0075, KAYARAD DN-2475, KAYARAD R-526, KAYARAD NPGDA, KAYARAD PEG400DA, KAYARAD MANDA, KAYARAD R-167, KAYARAD HX-220, KAYARAD HX620, KAYARAD R-551, KAYARAD R-712, KAYARAD R-604, KAYARAD R-684, KAYARAD GPO-303, KAYARAD TMPTA, KAYARAD THE-330, KAYARAD TPA-320, KAYARAD TPA-330, KAYARAD PET-30, KAYARAD RP-1040 (all manufactured by Nippon Kayaku Co., Ltd.); Aronix (registered trademark) M-210, Aronix M-208, Aronix M-211B, Aronix M-215, Aronix M-220, Aronix M-225, Aronix M-270, Aronix M-240, Aronix M-6100, Aronix M-6250, Aronix M-6500, Aronix M-6200, Aronix M-309, Aronix M-310, Aronix M-321, Aronix M-350, Aronix M-360, Aronix M-313, Aronix M-315, Aronix Aronix M-306, Aronix M-303, Aronix M-452, Aronix M-408, Aronix M-403, Aronix M-400, Aronix M-402, Aronix M-405, Aronix M-406, Aronix M-450, Aronix M-460, Aronix M-510, Aronix M-520, Aronix M-1100, Aronix M-1200, Aronix M-6100, Aronix M-6200, Aronix M-6250, Aronix M-6500, Aronix M-7100, Aronix M8030, Aronix M8060,Aronix M8100, Aronix M8530, Aronix M-8560, Aronix M9050 (all manufactured by Toyo Gosei Co., Ltd.); Viscoat 295, Viscoat 300, Viscoat 360, Viscoat GPT, Viscoat 3PA, Viscoat 400, Viscoat 260, Viscoat 312, Viscoat 335HP, Viscoat 700 (all manufactured by Osaka Organic Chemical Industry Co., Ltd.); A-200, A-400, A-600, A-1000, AB1206PE, ABE-300, A-BPE-10, A-BPE-20, A-BPE-30, A-BPE-4, A- BPEF, A-BPP-3, A-DCP, A-DOD-N, A-HD-N, A-NOD-N, APG-100, APG-200, APG-400, APG-700, A-PTMG-65, A-9300, A-9300-1CL, A-GLY-9E, A-GLY-20E, A-TM M-3, A-TMM-3L, A-TMM-3LM-N, A-TMPT, AD-TMP, ATM-35E, A-TMMT, A-9550, A-DPH, TMPT, 9PG, 701A, 1206PE, NPG, NOD-N, HD-N, DOD-N, DCP, BPE-1300N, BP E-900, BPE-200, BPE-100, BPE-80N, 23G, 14G, 9G, 4G, 3G, 2G, 1G (all manufactured by Shin-Nakamura Chemical Industry Co., Ltd.); Light Ester EG, Light Ester 2EG, Light Ester 3EG, Light Ester 4EG, Light Ester 9EG, Light Ester 14EG, Light Ester 1.4BG, Light Ester NP, Light Ester 1.6HX, Light Ester 1.9ND, Light Ester G-101P, Light Ester G-201P, Light Ester DCP-M, Light Ester BP-2EMK, Light Ester BP- 4EM, Light Ester BP-6EM, Light Ester TMP, Light Acrylate 3EG-A, Light Acrylate 4EG-A, Light Acrylate 9EG-A, Light Acrylate 14EG-A, Light Acrylate PTMGA-250, Light Acrylate NP-A, Light Acrylate MPD-A, Light Acrylate 1.6HX-A, Light Acrylate 1.9ND-A, Light Acrylate MOD-A, Light Acrylate DCP-A, Light Acrylate BP-4PA, Light Acrylate BA-134, Light Acrylate BP-10EA,Light Acrylate HPP-A, Light Acrylate G-201P, Light Acrylate TMP-A, Light Acrylate TMP-3EO-A, Light Acrylate TMP-6EO-3A, Light Acrylate PE-3A, Light Acrylate PE-4A, Light Acrylate DPE-6A, Epoxy Ester 40EM, Epoxy Ester 70PA, Epoxy Ester 200PA, Epoxy Ester 80MFA, Epoxy Ester 3002M, Epoxy Ester 3002A, Epoxy Ester 3000MK, Epoxy Ester 3000A, Epoxy Ester EX-0205, AH-600, AT-600, UA-306H, UA-306T, UA-306I, UA-510H, UF-8001G, DAUA-167 (Kyōryōsha Chemical Co., Ltd.); EBECRYL (registered trademark) TPGDA, EBECRYL 145, EBECRYL 150, EBECRYL PEG400DA, EBECRYL 11, EBECRYL HPNDA, EBECRYL PETIA, EBECRYL PETRA, EBECRYLTMPTA, EBECRYL TMPEOTA, EBECRYL OTA480, EBECRYL DPHA, EBECRYL 180, EBECRYL 40, EBECRYL 140, EBECRYL 204, EBECRYL 205, EBECRYL 210, EBECRYL 215, EBECRYL 220, EBECRYL 6202, EBECRYL 230, EBECRYL 244, EBECRYL 245, EBECRYL 264, EBECRYL 265, EBECRYL 270, EBECRYL 280 / 15IB, EBECRYL 284, EBECRYL 285, EBECRYL 294 / 25HD, EBECRYL1259, EBECRYL KRM8200, EBECRYL 4820, EBECRYL 4858, EBECRYL 5129, EBECRYL 8210, EBECRYL 8301, EBECRYL 8307, EBECRYL 8402, EBECRYL 8405, EBECRYL 8411, EBECRYL8804, EBECRYL 8807, EBECRYL 9260, EBECRYL 9270, EBECRYL KRM7735, EBECRYL KRM8296, EBECRYL KRM8452, EBECRYL 8311,EBECRYL 8701, EBECRYL 9227EA, EBECRYL 80, EBECRYL436, EBECRYL 438, EBECRYL 446, EBECRYL 450, EBECRYL 505, EBECRYL 524, EBECRYL 525, EBECRYL 770, EBECRYL 800, EBECRYL 810, EBECRYL 811, EBECRYL 812, EBECRYL 1830, EBECRYL 846, EBECRYL 851, EBECRYL 852, EBECRYL 853, EBECRYL 1870, EBECRYL 884, EBECRYL 885, EBECRYL 600, EBECRYL 605, EBECRYL 645, EBECRYL 648, EBECRYL 860, EBECRYL 1606, EBECRYL 3500, EBECRYL 3608, EBECRYL 3700, EBECRYL 3701, EBECRYL3702, EBECRYL 3703, EBECRYL 3708, EBECRYL 6040 (manufactured by Daicel Allnex Co., Ltd.); SR212, SR213, SR230, SR238F, SR259, SR268, SR272, SR306H, SR344, SR349, SR508, CD560, CD561, CD564, SR601, SR602, SR610, SR833S, SR9003, CD9043, SR9045, SR9209, SR205, SR206, SR209, SR210, SR214, SR231, S R239, SR248, SR252, SR297, SR348, SR480, CD540, CD541, CD542, SR603, SR644, SR9036, SR351S, SR368, SR415, SR444, S R454, SR492, SR499, CD501, SR502, SR9020, CD9021, SR9035, SR350, SR295, SR355, SR399, SR494, SR9041 (Sartomer company system). ,
[0057] The crosslinking compound of component (B) is used in combination of two or more. As a combination of two or more, a crosslinking compound having two polymerizable groups in one molecule and a crosslinking compound having three or more polymerizable groups in one molecule are preferred. As a crosslinking compound having three or more polymerizable groups in one molecule, a combination of two or more crosslinking compounds having different numbers of polymerizable groups may be used. In addition, as the polymerizable group, an acryloyloxy group or a methacryloyloxy group is preferred.
[0058] The content of the component (B) in the negative photosensitive resin composition of the present invention is 80% by mass to 90% by mass based on 100% by mass of the component (A).
[0059] <(C) Ingredients>
[0060] The component (C) in the negative photosensitive resin composition of the present invention is at least one photopolymerization initiator. The photopolymerization initiator of the component (C) is not particularly limited as long as it absorbs the light source used in photocuring.
[0061] Examples of the photopolymerization initiator include tert-butyl peroxy-isobutyrate, 2,5-dimethyl-2,5-bis(benzoyldioxy)hexane, 1,4-bis[α-(tert-butyldioxy)-isopropoxy]benzene, di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis(tert-butyldioxy)hexene hydroperoxide, α-(isopropylphenyl)-isopropyl hydroperoxide, tert-butyl hydroperoxide, 1,1-bis(tert-butyldioxy)-3,3,5-trimethylcyclohexane, butyl-4,4-bis(tert-butyldioxy)valerate, cyclohexanone peroxide, 2,2′,5,5′-tetra(tert-butyldioxy)pentanoate, and the like. Organic peroxides such as tert-butyl peroxycarbonyl)benzophenone, 3,3',4,4'-tetra(tert-butyl peroxycarbonyl)benzophenone, 3,3',4,4'-tetra(tert-amyl peroxycarbonyl)benzophenone, 3,3',4,4'-tetra(tert-hexyl peroxycarbonyl)benzophenone, 3,3'-bis(tert-butyl peroxycarbonyl)-4,4'-dicarboxybenzophenone, tert-butyl peroxybenzoate, di-tert-butyl diperoxyisophthalate; quinones such as 9,10-anthraquinone, 1-chloroanthraquinone, 2-chloroanthraquinone, octamethyl anthraquinone, 1,2-benzanthraquinone; benzoin methyl ether, benzoin ethyl ether, α-methyl benzoin derivatives such as α-phenylbenzoin, 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-1-[4-{4-(2-hydroxy-2-methyl-propionyl)benzyl}-phenyl]-2-methyl-propane-1-one, methyl benzoylformate, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one, 2-benzyl-2-dimethyl Alkyl phenone compounds such as amino-1-(4-morpholinophenyl)-1-butanone and 2-dimethylamino-2-(4-methyl-benzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one; acyl phosphine oxide compounds such as bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide and 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide; oxime ester compounds such as 2-(O-benzoyloxime)-1-[4-(phenylthio)phenyl]-1,2-octanedione and 1-(O-acetooxime)-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone.
[0062] The photopolymerization initiator can be obtained as a commercial product, and examples thereof include OMNIRAD (registered trademark) 651, OMNIRAD 184, OMNIRAD 500, OMNIRAD 2959, OMNIRAD 127, OMNIRAD 754, OMNIRAD 907, OMNIRAD 369, OMNIRAD 379, OMNIRAD 379EG, OMNIRAD 819, OMNIRAD 819DW, OMNIRAD 1700, OMNIRAD 1870, OMNIRAD 784, OMNIRAD 1173, OMNIRAD MBF, OMNIRAD 4265, and OMNIRAD TPO (all manufactured by IGM Resins Co., Ltd.) [formerly IRGACURE (registered trademark) 651, IRGACURE 184, IRGACURE 500、IRGACURE 2959、IRGACURE 127、IRGACURE 754、IRGACURE 907、IRGACURE 369、IRGACURE 379、IRGACURE 379EG、IRGACURE 819、IRGACURE 819DW、IRGACURE 1700、IRGACURE 1870、IRGACURE 784、IRGACURE 1173、IRGACURE MBF、IRGACURE 4265、IRGACURE TPO (above, manufactured by BASF Japan Co., Ltd.)]、IRGACURE (registered trademark) 1800、IRGACURE OXE01、IRGACURE OXE02 (above, manufactured by BASF Japan Co., Ltd.)、KAYACURE (registered trademark) DETX、KAYACURE MBP, KAYACURE DMBI, KAYACURE EPA, KAYACURE OA (all manufactured by Nippon Kayaku Co., Ltd.), VICURE-10, VICURE-55 (all manufactured by Stauffer Co., Ltd.), ESACURE (registered trademark) KIP150, ESACURE TZT, ESACURE 1001, ESACURE KTO46, ESACURE KB1, ESACURE KL200, ESACURE KS300, ESACURE EB3, TORONIC-PMS, TORONIC A, TORONIC B (above, manufactured by DKSH AGENT CO., LTD.), AMATIC Tomotron N-1717, Tomodo N-1414, Tomodo N-1606 (manufactured by ADEKA Co., Ltd.).
[0063] (C) The photopolymerization initiator of the component can be used alone or in combination of two or more.
[0064] The content of the component (C) in the negative photosensitive resin composition of the present invention is 3% by mass to 20% by mass based on 100% by mass of the total amount of the component (B).
[0065] <Solvent>
[0066] The negative photosensitive resin composition of the present invention contains a solvent. The solvent is not particularly limited as long as it is a solvent that dissolves the above-mentioned (A) component, (B) component, and (C) component.
[0067] Examples of the solvent include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, methyl cellosolve acetate, ethyl cellosolve acetate, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol propyl ether acetate, propylene glycol monobutyl ether, propylene glycol monobutyl ether acetate, toluene, xylene, methyl ethyl ketone, cyclopentanone, cyclohexanone, ethyl 2-hydroxypropionate, ethyl 2-hydroxy-2-methylpropionate, ethyl ethoxyacetate, ethyl hydroxyacetate, methyl 2-hydroxy-3-methylbutyrate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, ethyl 3-ethoxypropionate, methyl 3-ethoxypropionate, methyl pyruvate, ethyl acetate, butyl acetate, ethyl lactate, butyl lactate, 2-heptanone, and γ-butyrolactone.
[0068] Among the above solvents, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, 2-heptanone, ethyl lactate, butyl lactate, and cyclohexanone are preferred from the viewpoint of improving the leveling property of the coating film.
[0069] The above solvents can be used alone or in combination of two or more.
[0070] <Surfactant>
[0071] The negative photosensitive resin composition of the present invention may contain a surfactant for the purpose of improving coating properties. Examples of the surfactant include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether, and polyoxyethylene oleyl ether, polyoxyethylene alkyl aryl ethers such as polyoxyethylene octylphenyl ether and polyoxyethylene nonylphenyl ether, polyoxyethylene / polyoxypropylene block copolymers, sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan trioleate, and sorbitan tristearate. Sorbitol fatty acid esters, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan trioleate, polyoxyethylene sorbitan tristearate and other polyoxyethylene sorbitan fatty acid esters and other nonionic surfactants, EFTOP EF301 (registered trademark), EFTOP EF303, EFTOP EF352 (all manufactured by Mitsubishi Material Electronics Co., Ltd.), Megapac (registered trademark) Registered trademark) F-171, メガファックF-173, メガファックR-30, メガファックR-40, メガファックR-40-LM (above, manufactured by DIC Co., Ltd.), フロラードFC430, フロラードFC43 1 (Above, manufactured by Seryrotron Co., Ltd.), Seroton (registered trademark) AG710, Serono (Note Registered trademarks) S-382, サーフロンSC101, サーフロンSC102, サーフロンSC103, サーフFluorine-based surfactants such as LON SC104, SAFRON SC105, SAFRON SC106 (manufactured by AGC Corporation), FTX-206D, FTX-212D, FTX-218, FTX-220D, FTX-230D, FTX-240D, FTX-212P, FTX-220P, FTX-228P, and FTX-240G (manufactured by Neos Corporation), and organosiloxane polymer KP341 (manufactured by Shin-Etsu Chemical Co., Ltd.).
[0072] The above-mentioned surfactant can be used alone or in combination of two or more. In addition, when the above-mentioned surfactant is used, its content in the negative photosensitive resin composition of the present invention is 3% by mass or less based on the content in the solid content of the composition, for example, 0.0001% by mass to 3% by mass, preferably 0.001% by mass to 1% by mass, and more preferably 0.01% by mass to 0.5% by mass.
[0073] <Other additives>
[0074] The negative photosensitive resin composition of the present invention may contain a curing aid, ultraviolet absorber, sensitizer, plasticizer, antioxidant, adhesion aid, or dissolution promoter such as polyphenol or polycarboxylic acid as other additives as necessary, unless the effects of the present invention are impaired.
[0075] <Method for preparing the composition>
[0076] The preparation method of the negative photosensitive resin composition of the present invention is not particularly limited, and examples thereof include a method of dissolving the alkali-soluble polymer of the component (A) in the above-mentioned solvent, and mixing the crosslinking compound of the component (B) and the photopolymerization initiator of the component (C) in a predetermined ratio in the obtained solution to prepare a uniform solution. Furthermore, examples thereof include a method of further adding and mixing the above-mentioned other additives as needed at an appropriate stage of the preparation method.
[0077] <Use of negative photosensitive resin composition>
[0078] The negative photosensitive resin composition of the present invention is applied on a substrate [for example, a semiconductor substrate such as silicon coated with a silicon oxide film, a semiconductor substrate such as silicon coated with a silicon nitride film or a silicon nitride oxide film, a silicon nitride substrate, a quartz substrate, a glass substrate (including alkali-free glass, low-alkali glass, crystallized glass), a glass substrate formed with an indium tin oxide (ITO) film] by an appropriate coating method such as a spin coater or a coater, and then pre-baked using a heating device such as a hot plate to form a coating film.
[0079] The pre-baking conditions are appropriately selected from a baking temperature of 80° C. to 150° C. and a baking time of 0.3 to 60 minutes. Preferably, the baking temperature is 80° C. to 100° C. and the baking time is 0.5 to 5 minutes.
[0080] Moreover, as a film thickness of the film formed from the negative photosensitive resin composition of the present invention, for example, is 0.005 μm to 20 μm, or preferably 0.01 μm to 15 μm.
[0081] Next, the obtained film is exposed through a mask (intermediate mask) for forming a predetermined pattern. For example, g-rays, i-rays, or KrF excimer lasers can be used for exposure. After exposure, post-exposure baking is performed as required. As the conditions for post-exposure baking, a heating temperature of 80° C. to 100° C. and a heating time of 0.3 minutes to 60 minutes are appropriately selected. Furthermore, development is performed with an alkaline developer.
[0082] Examples of the alkaline developer include aqueous solutions of alkali metal hydroxides such as potassium hydroxide and sodium hydroxide, aqueous solutions of quaternary ammonium hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, and choline, and aqueous solutions of amines such as ethanolamine, propylamine, and ethylenediamine. Furthermore, a surfactant may be added to these developers.
[0083] The conditions for development are appropriately selected from a development temperature of 5° C. to 50° C. and a development time of 10 seconds to 300 seconds. The film formed from the negative photosensitive resin composition of the present invention can be easily developed at room temperature using an aqueous solution of tetramethylammonium hydroxide. After development, the film can be appropriately rinsed using, for example, ultrapure water as a rinse liquid.
[0084] Then, the developed film is exposed to light on the entire surface using, for example, g-rays, i-rays, or KrF excimer lasers. Furthermore, the developed film may be post-baked using a heating device such as a hot plate before or after the entire surface exposure. The post-baking conditions may be appropriately selected from, for example, a baking temperature of 80° C. to 100° C. and a baking time of 0.5 to 60 minutes.
[0085] Example
[0086] Hereinafter, the present invention will be described in more detail with reference to synthesis examples and examples, but the present invention is not limited to the following examples.
[0087] [Measurement of weight average molecular weight]
[0088] Equipment: GPC system manufactured by JASCO Corporation
[0089] Column: Shodex [registered trademark] GPC KF-804L and GPC KF-803L
[0090] Column oven: 40°C
[0091] Flow rate: 1ml / min
[0092] Eluent: Tetrahydrofuran
[0093] Standard sample: polystyrene
[0094] [Synthesis example 1]
[0095] After dissolving 60 g of methacrylic acid, 240 g of methyl methacrylate, and 7.6 g of 2,2'-azobisisobutyronitrile in 132 g of propylene glycol monomethyl ether, the solution was added dropwise to a flask in which 440 g of propylene glycol monomethyl ether was maintained at 70°C for 3 hours. After the addition was completed, the reaction was carried out for 18 hours to obtain a solution of an alkali-soluble polymer (copolymer) having a structural unit represented by the following formula (1b-1) and a structural unit represented by the following formula (2a-1) (solid content concentration 35% by mass). The weight average molecular weight Mw of the obtained copolymer was 35,000 (polystyrene conversion).
[0096]
[0097] [Synthesis example 2]
[0098] After dissolving 61 g of methacrylic acid, 122 g of methyl methacrylate, 122 g of styrene, and 7.6 g of 2,2'-azobisisobutyronitrile in 134 g of propylene glycol monomethyl ether, the solution was added dropwise to a flask in which 446 g of propylene glycol monomethyl ether was maintained at 70°C for 3 hours. After the addition was completed, the reaction was carried out for 18 hours to obtain a solution (solid content concentration 35% by mass) of an alkali-soluble polymer (terpolymer) having a structural unit represented by the following formula (1b-1), a structural unit represented by the following formula (2a-1), and a structural unit represented by the following formula (2b-1). The weight average molecular weight Mw of the obtained copolymer was 35,000 (polystyrene conversion).
[0099]
[0100] [Example 1]
[0101] 19.7 g of the solution of the alkali-soluble polymer obtained in Synthesis Example 1 (solid content concentration: 35% by mass) as the component (A), 3.4 g of PET-30 (manufactured by Nippon Kayaku Co., Ltd.) and 2.1 g of ABE-300 (manufactured by Shin-Nakamura Chemical Co., Ltd.) as the crosslinking compound as the component (B), 0.21 g of IRGACURE (registered trademark) OXE01 (manufactured by BASF Japan Co., Ltd.) and OMNIRAD (registered trademark) 184 (manufactured by IGM) as the photopolymerization initiator as the component (C) were mixed. 0.62 g of propylene glycol monomethyl ether (manufactured by Resins Co., Ltd.) [former IRGACURE (registered trademark) 184 (manufactured by BASF Japan Co., Ltd.)] and 0.0040 g of DFX-18 (manufactured by Neos Co., Ltd.) as a surfactant were dissolved in 5.6 g of propylene glycol monomethyl ether and 18.4 g of propylene glycol monomethyl ether acetate to prepare a solution. Then, the solution was filtered using a polyethylene microfilter with a pore size of 1 μm to prepare a negative photosensitive resin composition.
[0102] [Example 2]
[0103] 19.6 g of the solution of the alkali-soluble polymer (solid content concentration 35% by mass) obtained in Synthesis Example 1 as component (A), 4.1 g of PET-30 (manufactured by Nippon Kayaku Co., Ltd.) and 2.1 g of ABE-300 (manufactured by Shin-Nakamura Chemical Co., Ltd.) as crosslinking compounds as component (B), 0.21 g of IRGACURE (registered trademark) OXE01 (manufactured by BASF Japan Co., Ltd.) as a photopolymerization initiator as component (C), and 0.0040 g of DFX-18 (manufactured by Neos Co., Ltd.) as a surfactant were dissolved in 5.6 g of propylene glycol monomethyl ether and 18.4 g of propylene glycol monomethyl ether acetate to prepare a solution. Then, the solution was filtered using a polyethylene microfilter having a pore size of 1 μm to prepare a negative photosensitive resin composition.
[0104] [Example 3]
[0105] 18.8 g of the solution of the alkali-soluble polymer obtained in Synthesis Example 1 (solid content concentration: 35% by mass) as the component (A), 3.9 g of PET-30 (manufactured by Nippon Kayaku Co., Ltd.) and 2.0 g of ABE-300 (manufactured by Shin-Nakamura Chemical Co., Ltd.) as the crosslinking compound as the component (B), 0.20 g of IRGACURE (registered trademark) OXE01 (manufactured by BASF Japan Co., Ltd.) and OMNIRAD (registered trademark) 184 (manufactured by IGM) as the photopolymerization initiator as the component (C) were mixed. 0.59 g of propylene glycol monomethyl ether (manufactured by Resins Co., Ltd.) [former IRGACURE (registered trademark) 184 (manufactured by BASF Japan Co., Ltd.)] and 0.0040 g of DFX-18 (manufactured by Neos Co., Ltd.) as a surfactant were dissolved in 6.2 g of propylene glycol monomethyl ether and 18.4 g of propylene glycol monomethyl ether acetate to prepare a solution. Then, the solution was filtered using a polyethylene microfilter with a pore size of 1 μm to prepare a negative photosensitive resin composition.
[0106] [Example 4]
[0107] 23.7 g of the solution of the alkali-soluble polymer obtained in Synthesis Example 2 (solid content concentration: 35% by mass) as the component (A), 5.0 g of PET-30 (manufactured by Nippon Kayaku Co., Ltd.) and 2.5 g of ABE-300 (manufactured by Shin-Nakamura Chemical Co., Ltd.) as the crosslinking compound as the component (B), 0.25 g of IRGACURE (registered trademark) OXE01 (manufactured by BASF Japan Co., Ltd.) and OMNIRAD (registered trademark) 184 (manufactured by IGM) as the photopolymerization initiator as the component (C) were mixed. 0.75 g of propylene glycol monomethyl ether (manufactured by Resins Co., Ltd.) [former IRGACURE (registered trademark) 184 (manufactured by BASF Japan Co., Ltd.)] and 0.0050 g of DFX-18 (manufactured by Neos Co., Ltd.) as a surfactant were dissolved in 1.2 g of propylene glycol monomethyl ether and 16.6 g of propylene glycol monomethyl ether acetate to prepare a solution. Then, the solution was filtered using a polyethylene microfilter with a pore size of 1 μm to prepare a negative photosensitive resin composition.
[0108] [Comparative Example 1]
[0109] 20.8 g of the solution of the alkali-soluble polymer obtained in Synthesis Example 1 (solid content concentration: 35% by mass) as the component (A), 2.9 g of PET-30 (manufactured by Nippon Kayaku Co., Ltd.) and 2.2 g of ABE-300 (manufactured by Shin-Nakamura Chemical Co., Ltd.) as the crosslinking compound as the component (B), 0.22 g of IRGACURE (registered trademark) OXE01 (manufactured by BASF Japan Co., Ltd.) and OMNIRAD (registered trademark) 184 (manufactured by IGM) as the photopolymerization initiator as the component (C) were mixed. 0.65 g of IRGACURE (registered trademark) 184 (manufactured by BASF Japan Co., Ltd.) and 0.0040 g of DFX-18 (manufactured by Neos Co., Ltd.) as a surfactant were dissolved in 4.9 g of propylene glycol monomethyl ether and 18.4 g of propylene glycol monomethyl ether acetate to prepare a solution. Then, the solution was filtered using a polyethylene microfilter with a pore size of 1 μm to prepare a negative photosensitive resin composition. The content of the component (B) of the negative photosensitive resin composition of this comparative example is outside the scope of the present invention.
[0110] [Comparative Example 2]
[0111] 15.6 g of the solution of the alkali-soluble polymer obtained in Synthesis Example 1 as component (A) (solid content concentration 35% by mass), 3.3 g of PET-30 (manufactured by Nippon Kayaku Co., Ltd.) and 3.3 g of ABE-300 (manufactured by Shin-Nakamura Chemical Co., Ltd.) as crosslinking compounds as component (B), 1.3 g of IRGACURE (registered trademark) OXE01 (manufactured by BASF Japan Co., Ltd.) as a photopolymerization initiator as component (C), and 0.0040 g of DFX-18 (manufactured by Neos Co., Ltd.) as a surfactant were dissolved in 8.3 g of propylene glycol monomethyl ether and 18.5 g of propylene glycol monomethyl ether acetate to prepare a solution. Then, the solution was filtered using a polyethylene microfilter with a pore size of 1 μm to prepare a negative photosensitive resin composition. The content of the component (B) of the negative photosensitive resin composition of this comparative example is outside the range of the present invention.
[0112] [Comparative Example 3]
[0113] 24.5 g of the solution of the alkali-soluble polymer (solid content concentration 35% by mass) obtained in Synthesis Example 1 as component (A), 4.3 g of PET-30 (manufactured by Nippon Kayaku Co., Ltd.) as a crosslinking compound as component (B), 0.13 g of IRGACURE (registered trademark) OXE01 (manufactured by BASF Japan Co., Ltd.) as a photopolymerization initiator as component (C), and 0.0039 g of DFX-18 (manufactured by Neos Co., Ltd.) as a surfactant were dissolved in 2.6 g of propylene glycol monomethyl ether and 18.5 g of propylene glycol monomethyl ether acetate to prepare a solution. Then, the solution was filtered using a polyethylene microfilter with a pore size of 1 μm to prepare a negative photosensitive resin composition. The content of the component (B) of the negative photosensitive resin composition of this comparative example is outside the scope of the present invention, and the component (B) does not contain a crosslinking compound having two polymerizable groups in one molecule.
[0114] [Comparative Example 4]
[0115] 23.2 g of the solution of the alkali-soluble polymer (solid content concentration 35% by mass) obtained in Synthesis Example 1 as component (A), 4.1 g of PET-30 (manufactured by Nippon Kayaku Co., Ltd.) as a crosslinking compound as component (B), 0.8 g of IRGACURE (registered trademark) OXE01 (manufactured by BASF Japan Co., Ltd.) as a photopolymerization initiator as component (C), and 0.0039 g of DFX-18 (manufactured by Neos Co., Ltd.) as a surfactant were dissolved in 3.4 g of propylene glycol monomethyl ether and 18.5 g of propylene glycol monomethyl ether acetate to prepare a solution. Then, the solution was filtered using a polyethylene microfilter with a pore size of 1 μm to prepare a negative photosensitive resin composition. The content of the component (B) of the negative photosensitive resin composition of this comparative example is outside the scope of the present invention, and the component (B) does not contain a crosslinking compound having two polymerizable groups in one molecule.
[0116] [Comparative Example 5]
[0117] 19.5 g of the solution of the alkali-soluble polymer obtained in Synthesis Example 1 as component (A) (solid content concentration 35% by mass), 4.1 g of PET-30 (manufactured by Nippon Kayaku Co., Ltd.) and 2.0 g of ABE-300 (manufactured by Shin-Nakamura Chemical Co., Ltd.) as crosslinking compounds as component (B), 0.061 g of IRGACURE (registered trademark) OXE01 (manufactured by BASF Japan Co., Ltd.) as a photopolymerization initiator as component (C), and 0.0039 g of DFX-18 (manufactured by Neos Co., Ltd.) as a surfactant were dissolved in 5.9 g of propylene glycol monomethyl ether and 18.5 g of propylene glycol monomethyl ether acetate to prepare a solution. Then, the solution was filtered using a polyethylene microfilter with a pore size of 1 μm to prepare a negative photosensitive resin composition. The content of the component (C) of the negative photosensitive resin composition of this comparative example is outside the range of the present invention.
[0118] [Comparative Example 6]
[0119] 17.1 g of the solution of the alkali-soluble polymer obtained in Synthesis Example 1 as component (A) (solid content concentration 35% by mass), 3.6 g of PET-30 (manufactured by Nippon Kayaku Co., Ltd.) and 1.8 g of ABE-300 (manufactured by Shin-Nakamura Chemical Co., Ltd.) as crosslinking compounds as component (B), 1.6 g of IRGACURE (registered trademark) OXE01 (manufactured by BASF Japan Co., Ltd.) as a photopolymerization initiator as component (C), and 0.0039 g of DFX-18 (manufactured by Neos Co., Ltd.) as a surfactant were dissolved in 7.4 g of propylene glycol monomethyl ether and 18.5 g of propylene glycol monomethyl ether acetate to prepare a solution. Then, the solution was filtered using a polyethylene microfilter with a pore size of 1 μm to prepare a negative photosensitive resin composition. The content of the component (C) in the negative photosensitive resin composition of this comparative example is outside the range of the present invention.
[0120] [Comparative Example 7]
[0121] 24.9 g of a solution of the alkali-soluble polymer obtained in Synthesis Example 2 as component (A) (solid content concentration: 35% by mass), 5.3 g of PET-30 (manufactured by Nippon Kayaku Co., Ltd.) as a crosslinking compound as component (B), 0.26 g of IRGACURE (registered trademark) OXE01 (manufactured by BASF Japan Co., Ltd.) as a photopolymerization initiator and 0.78 g of OMNIRAD (registered trademark) 184 (manufactured by IGM Resins Co., Ltd.) [formerly IRGACURE (registered trademark) 184 (manufactured by BASF Japan Co., Ltd.)] as component (C), and 0.0045 g of DFX-18 (manufactured by Neos Co., Ltd.) as a surfactant were dissolved in 1.3 g of propylene glycol monomethyl ether and 17.5 g of propylene glycol monomethyl ether acetate to prepare a solution. The negative photosensitive resin composition of this comparative example contained component (B) outside the scope of the present invention and did not contain a crosslinking compound having two polymerizable groups in one molecule.
[0122] [Transmittance measurement]
[0123] The negative photosensitive resin compositions prepared in Examples 1 to 4 and Comparative Examples 1 to 7 were applied onto a quartz substrate using a spin coater and prebaked on a hot plate at 100° C. for 90 seconds to form resin films having the film thicknesses shown in Table 1. Next, an ultraviolet irradiation device PLA-501(F) (manufactured by Kinon Corporation) was used to irradiate the substrate at a wavelength of 365 nm at a dose of 1000 mJ / cm 2The entire surface of the resin film was irradiated with ultraviolet rays. Then, the resin film was post-baked on a hot plate at 100°C for 5 minutes. Furthermore, an intermittent UV irradiation device (high-pressure mercury lamp 2kW×1 lamp) (manufactured by Iglabix Co., Ltd.) was used to set the exposure amount at 365nm to 1000mJ / cm 2 The entire surface of the resin film was irradiated with ultraviolet rays, thereby forming a cured film on the quartz substrate. The pre-baking and post-baking were both performed in the atmosphere. For these cured films, the transmittance was measured by changing the wavelength by 2 nm at a time in the range of 400 nm to 800 nm using an ultraviolet-visible spectrophotometer UV-2550 (manufactured by Shimadzu Corporation). The minimum transmittance values measured in the range of 400 nm to 800 nm are shown in Table 2. It is shown that the closer the value is to 100%, the more transparent the film can be obtained.
[0124] [Solvent resistance test]
[0125] The negative photosensitive resin compositions prepared in Examples 1 to 4 and Comparative Examples 1 to 7 were applied onto silicon wafers using a spin coater and prebaked on a hot plate at 100° C. for 90 seconds to form resin films having the film thicknesses shown in Table 1. Subsequently, the compositions were irradiated with an ultraviolet radiation device PLA-501(F) (manufactured by Kinon Corporation) at a wavelength of 365 nm and a dose of 1000 mJ / cm 2 The entire surface of the resin film was irradiated with ultraviolet rays. Then, the resin film was developed for 60 seconds using an aqueous solution of tetramethylammonium hydroxide (TMAH) of a concentration shown in Table 1 as an alkaline developer, rinsed with ultrapure water for 20 seconds, and dried. As a result, the resin film formed by the negative photosensitive resin composition prepared in Comparative Examples 3 and 5 was removed from the silicon wafer. Furthermore, the remaining resin film was post-baked on a hot plate at 100°C for 5 minutes. Finally, an intermittent UV irradiation device (high-pressure mercury lamp 2kW×1 lamp) (manufactured by Igraphix Co., Ltd.) was used to expose the film at 365nm with an exposure amount of 1000mJ / cm 2The ultraviolet rays were irradiated to the entire surface of the resin film, thereby forming a cured film on the silicon wafer. The pre-baking and post-baking were both carried out in the atmosphere. These cured films were immersed in propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, ethyl lactate, methyl 3-methoxypropionate, and 2.38% by mass tetramethylammonium hydroxide (TMAH) aqueous solution at a temperature of 23°C for 2 minutes. The film thickness change of the cured film was measured before and after the immersion. If one of the solvents used in the immersion test showed a film thickness increase or decrease of more than 10% relative to the film thickness of the cured film before immersion, it was recorded as "×", if the film thickness increase or decrease was less than 10% and more than 5%, it was recorded as "△", if the film thickness increase or decrease was less than 5% for all solvents, it was recorded as "○", and if it could not be measured, it was recorded as "-", and the solvent resistance was evaluated. The evaluation results are shown in Table 2.
[0126] [Residual film rate, sensitivity and residue evaluation]
[0127] The negative photosensitive resin compositions prepared in Examples 1 to 4 and Comparative Examples 1 to 7 were respectively coated on silicon wafers using a spin coater and pre-baked on a hot plate at 100°C for 90 seconds to form resin films of the thickness shown in Table 1. The above prebaking was carried out in the atmosphere. The film thickness of these resin films was measured using an optical interference film thickness measuring device, Lamdace VM-2110 (manufactured by SCREEN Semiconductor Solutions Co., Ltd.). Next, the above resin film was exposed through a binary mask using an i-ray stepper exposure machine NSR-2205i12D (NA=0.63) (manufactured by Nikon Co., Ltd.). Then, the resin film was developed for 60 seconds using a tetramethylammonium hydroxide (TMAH) aqueous solution of the concentration shown in Table 1 as an alkaline developer, rinsed with ultrapure water for 20 seconds, and dried. As a result, a rectangular pattern of 7 mm × 7 mm was formed on the silicon wafer from the resin film formed by the negative photosensitive resin composition prepared in Examples 1 to 4, Comparative Examples 1, 2, 4, 6, and 7. On the other hand, the rectangular pattern was not formed from the resin film formed by the negative photosensitive resin composition prepared in Comparative Examples 3 and 5. The film thickness of the formation on the silicon wafer was measured using the same method as the film thickness measurement of the resin film. The residual film rate (%) was evaluated compared with the film thickness of the resin film just after pre-baking. The results are shown in Table 2. The residual film rate is calculated by the formula (film thickness after development / film thickness after pre-baking) × 100, showing that the closer its value is to 100%, the less easily the exposed part of the resin film is dissolved in the developer, so it is preferred.
[0128] Furthermore, the minimum exposure dose at which the residual film rate is the largest was evaluated. The results are shown in Table 2. 2 When the residual film ratio did not reach the maximum, or when a rectangular pattern of 7 mm×7 mm was not formed, it was regarded as impossible to measure and expressed as “-.” This indicates that the smaller the minimum exposure amount, the higher the sensitivity of the resin film.
[0129] Furthermore, the film thickness of the unexposed portion of the resin film was measured using an optical interference film thickness measuring device, Lamdace VM-2110 (manufactured by SCREEN Semiconductor Sound Systems). It was shown that the thinner the film thickness, the less the residue. When the film thickness was 10 nm or more, it was recorded as "×", when it was less than 10 nm and 5 nm or more, it was recorded as "△", and when it was less than 5 nm, it was recorded as "○", and the residue was evaluated. The evaluation results are shown in Table 2.
[0130] [Table 1]
[0131] Table 1
[0132]
[0133] [Table 2]
[0134] Table 2
[0135]
Claims
1. A method for producing a microlens, comprising the following steps: a step of coating a negative photosensitive resin composition for forming a microlens on a substrate and pre-baking it at 80 to 100° C. to form a resin film; a step of exposing the resin film through a mask; a step of developing the exposed resin film using an alkaline developer; a step of exposing the entire surface of the developed resin film; and a step of post-baking the resin film at 80 to 100° C. before or after the step of exposing the entire surface of the developed resin film. The negative photosensitive resin composition for forming a microlens contains the following component (A), 80% to 90% by mass of the following component (B) relative to 100% by mass of the component (A), 3% to 20% by mass of the following component (C) relative to 100% by mass of the total amount of the component (B), and a solvent. (A) ingredient: alkali-soluble polymer, (B) component: at least two crosslinking compounds having two or more polymerizable groups selected from acryloyloxy and methacryloyloxy groups in one molecule, wherein the at least two crosslinking compounds include a crosslinking compound having two of the polymerizable groups in one molecule and a crosslinking compound having three or more of the polymerizable groups in one molecule, and the crosslinking compound having three or more of the polymerizable groups in one molecule is a combination of two or more crosslinking compounds having different numbers of the polymerizable groups, (C) Component: at least one photopolymerization initiator. 2 . The method for producing a microlens according to claim 1 , wherein the polymerizable group is an acryloxy group.
3. The method for producing a microlens according to claim 1 or 2, wherein the alkali-soluble polymer has a structural unit selected from the following formula (1a), formula (1b), formula (1c), formula (1d) and formula (1e), In the formula, R 1 represents a hydrogen atom or a methyl group, A represents an -O- group or an -NH- group, X represents a single bond, an alkylene group having 1 to 3 carbon atoms, or a divalent linking group containing an alkyleneoxy group having 1 to 3 carbon atoms, and Z 1 represents hydroxyphenyl or carboxyphenyl, Z 2 represents hydroxyphenyl, carboxyphenyl or carboxyl, Z 3 represents a hydrogen atom, a hydroxyphenyl group or a carboxyphenyl group.
4. The method for producing a microlens according to claim 3, wherein the alkali-soluble polymer is a copolymer further having a structural unit different from the structural unit and selected from the following formula (2a), formula (2b) and formula (2c), In the formula, R 1 , A and X have the same meanings as those defined in claim 3, and Z 4 It represents a linear organic group having 1 to 3 carbon atoms, or a branched or cyclic organic group having 3 to 14 carbon atoms.
Citation Information
Patent Citations
Interphone with monitor
JP1981073963A
The paper container spout opening method
JP1983067735U
Manufacture of solid-state image sensing device
JP1989010666A
On-chip lens and manufacture thereof
JP1994112459A
Negative photosensitive resin composition
CN105765458A